POSTKOLONIALNA ANALIZA TWÓRCZOŚCI OŁEKSIJA CZUPY - Kupidura, Ryszard (Studia Ukrainica Posnaniensia, 2016)
This article is an attempt of the post-colonial reading of Oleksiy Chupa’s novels, a writer from Makiivka. In his three books published in 2014 — 10 Words about Homeland, The Homeless of Donbass and Stories from my Shelter — the author of this paper tries to fi nd the answers to the questions about the functioning of Ukrainian literary tradition, the creation of the fi ction post-industrial space, as well as the identity of the eastern regions of Ukraine.